Nutritional education program for fatty liver disease associated with metabolic dysfunction for Primary Health Care physicians - Mirian Belkis Nápoles Valdés; Manuel Horta Sánchez; Miguel Angel Amaró Garrido; Tania Santos (Gaceta Médica Espirituana)
Background: insufficiencies in nutritional education by Primary Health Care physicians may influence the inadequate management of fatty liver disease associated with metabolic dysfunction.